Conduct of vaccination in hard-to-reach areas to address potential polio reservoir areas, 2014-2015 - Samuel Bawa; Faisal Shuaib; Mahmoud Saidu; Adamu Ningi; Suleiman Abdullahi; Bashir Abba; Audu Idowu; Jibrin Alkasim; Kulchumi Hammanyero; Charity Warigon; Sisay G. Tegegne; Richard Banda; et al. (BMC, 2018)
Abstract Background The Global Vaccine Action Plan (GVAP) seeks to achieve the total realization of its vision through equitable access to immunization as well as utilizing the immunization systems for delivery of other primary healthcare programs. The inequities in accessing hard-to-reach areas have very serious implications for the prevention and control of vaccine-preventable diseases, especially the polio eradication initiative. The Government of Nigeria implemented vaccination in hard-to-reach communities with support from the World Health Organization (WHO) to address the issues of health inequities in the hard-to-reach communities. This paper documents the process of conducting integrated mobile vaccination in these hard-to-reach areas and the impact on immunization outcomes. Methods We conducted vaccination using mobile health teams in 2311 hard-to-reach settlements in four states at risk of sustaining polio transmission in Nigeria from July 2014 to September 2015. Results The oral polio vaccine (OPV)3 coverage among children under 1 year of age improved from 23% at baseline to 61% and OPV coverage among children aged 1-5 years increased from 60 to 90%, while pentavalent vaccine (penta3) coverage increased from 22 to 55%. Vitamin A was administered to 78% of the target population and 9% of children that attended the session were provided with treatment for malaria. Conclusions The hard-to-reach project has improved population immunity against polio, as well as other routine vaccinations and delivery of child health survival interventions in the hard-to-reach and underserved communities.